Point made : how to write like the nation's top advocates - Guberman, Ross (Oxford University Press, 2014)
"With Point Made, legal writing expert Ross Guberman throws a life preserver to attorneys, who are under more pressure than ever to produce compelling prose. What is the strongest opening for a motion or brief? How to draft winning headings? How to tell a persuasive story when the record is dry and dense? The answers are 'more science than art, ' says Guberman, who has analyzed stellar arguments by distinguished attorneys to develop step-by-step instructions for achieving the results you want. The author takes an empirical approach, drawing heavily on the writings of the nation's 50 most influential lawyers, including Barack Obama, John Roberts, Elena Kagan, Ted Olson, and David Boies. Their strategies, demystified and broken down into specific, learnable techniques, become a detailed writing guide full of practical models ..."--Publisher's information